2019
DOI: 10.1111/jfpe.13150
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between microwave‐cooking and steam‐cooking on starch properties and in vitro starch digestibility of cooked pigmented rice

Abstract: The influence of two types of cooking method, that is, steam‐cooking and microwave‐cooking, on the morphological structure, starch fractions, and starch digestibility of cooked Thai pigmented rice (three cultivars) was examined. The relationship between starch hydrolysis and change in X‐ray diffraction (XRD) pattern, including the change of crystallinity degree during in vitro digestion, was also investigated. The results indicated that the cooked rice morphological structure and starch hydrolysis rate during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…The X-ray diffraction patterns of unbaked WF and RB flour exhibited a typical A-type XRD pattern with the diffraction peaks at 2h = 15°, 17°, 18°and 23°(Fig. 2), which corresponds with that of cereal starches (Thuengtung et al 2019). The crystallinity of WF was significantly higher than RB.…”
Section: Xrd Analysismentioning
confidence: 93%
“…The X-ray diffraction patterns of unbaked WF and RB flour exhibited a typical A-type XRD pattern with the diffraction peaks at 2h = 15°, 17°, 18°and 23°(Fig. 2), which corresponds with that of cereal starches (Thuengtung et al 2019). The crystallinity of WF was significantly higher than RB.…”
Section: Xrd Analysismentioning
confidence: 93%
“…Furthermore, the stickiness between cooked rice grains was strongly affected by the molecular structure of the leached starch [ 16 ]. One study also reported that cooked rice’s morphological structure and in vitro digestion rate was varied by cooking method [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Heat treatment is carried out over the entire volume of the material, its organoleptic characteristics, disinfection, and destruction of pests are improved (Yan et al, 2018). Due to the high percentage of equilibrium starch hydrolysis after microwave pretreatment, the digestibility of grain by animals can be increased (Khattab, Arntfield, & Nyachoti, 2009; Thuengtung, Matsushita, & Ogawa, 2019).…”
Section: Introductionmentioning
confidence: 99%